PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE INSTANT ASSESSMENT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 25 PADANG - Baspan, Ficko Murieka; Haryono, Yulia; Pratiwi, Merina (Pendidikan Matematika, 2013)
The introduction of this research was the low of studentsâ understanding of mathematical concept and low of students activities. The purposes of this research was to determine studentsâ understanding of mathematical concept and students activities by applying active learning type instant assessment was better than studentsâ understanding of mathematical concept and students activities by applying conventional teaching class VIII of SMPN 25 Padang. Design of this research was experimental research random on the subject. The populations in this study was student of class VIII, the sample was class VIII.10 as the exsperimental class and the control class VIII.6. instruments in this study was a observation sheet and final test with essay. Data analysis was performed with the MINITABâS program obtained p-value was less than Î±, the hyphothesis was accepted. It can be concluded the studentsâ understanding of mathematical concept and students activities by inplementing active learning type instant assessment better than studentsâ understanding mathematical concept and students activities by applying conventional teaching class VIII SMPN 25 Padang.